The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/foods9010007
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-QTOF/MS Characterization of Phenolic Compounds from Medicinal Plants (Hops and Juniper Berries) and Their Antioxidant Activity

Abstract: Hops (Humulus lupulus L.) and juniper berries (Juniperus communis L.) are two important medicinal plants widely used in the food, beverage, and pharmaceutical industries due to their strong antioxidant capacity, which is attributed to the presence of polyphenols. The present study is conducted to comprehensively characterize polyphenols from hops and juniper berries using liquid chromatography coupled with electrospray-ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF/MS) to assess their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 33 publications
7
74
0
Order By: Relevance
“…Compound 54 was identified as kaempferol glycoside ( m / z = 447). Both have already been reported in H. italicum before [ 22 , 28 , 29 ]. Compound 61 , with a molecular ion at m / z = 489 and a fragment ion [M−H-204] − at m / z = 285 produced after acetylhexoside loss, was therefore identified as kaempferol acetylglycoside, which is reported here for the first time.…”
Section: Resultsmentioning
confidence: 52%
“…Compound 54 was identified as kaempferol glycoside ( m / z = 447). Both have already been reported in H. italicum before [ 22 , 28 , 29 ]. Compound 61 , with a molecular ion at m / z = 489 and a fragment ion [M−H-204] − at m / z = 285 produced after acetylhexoside loss, was therefore identified as kaempferol acetylglycoside, which is reported here for the first time.…”
Section: Resultsmentioning
confidence: 52%
“…The 70% ethanol extract of unripe J. excelsa galbuli from location 3 also showed the highest antioxidant potential by copper reduction assay—473.9 mM TE/g dw. Antioxidant capacity can vary and depends on the sample and the nature and type of solvent extraction [ 56 ]. In general, it was reported that ethanol extract of J. communis showed better scavenging activity in the FRAP assay among five different Juniperus species , including J. communis , J. excelsa , J. foetidissima , J. oxycedrus , and J. sabina [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the phenolic estimation in selected fruit peel samples, TPC, TFC, and TTC assays were performed, while for measuring their antioxidant capacities, four different types of antioxidant assays including FRAP, DPPH, ABTS, and TAC were performed by adopting our previously published methods of Tang, et al [ 20 ], explained in the supplementary material . The data was determined using a Multiskan ® Go microplate photometer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%